1986
DOI: 10.1203/00006450-198601000-00008
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Surgery on the Nitrogen Metabolism of Parenterally Fed Human Neonates

Abstract: ABSTRACT. Nitrogen retention and rates of whole body whole body protein synthes~s, we hypothesized that giving inamino nitrogen flux, protein synthesis, and breakdown were creased amounts of exogenous amino acids as precursor might measured in 18 neonates during the 72 h immediately reverse this process and improve net prot~in synthesis. We therepostsurgery. The infants were all intravenously fed with a fore studied neonates receiving either 2.5 g or 4.0 g/kg/day of crystalline amino acid source (Vamin), gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 10 publications
2
22
0
Order By: Relevance
“…Exogenous protein and caloric provisions through parenteral nutrition help to increase the synthesis of new protein but have little effect on the body's increased protein degradation. 4,5 Excessive caloric allotments may increase CO 2 production rates and thereby exacerbate the ventilatory burden of the child. 6 One study of ECMO neonates has shown a possible paradoxical increase in protein breakdown with the administration of increased carbohydrate regimens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exogenous protein and caloric provisions through parenteral nutrition help to increase the synthesis of new protein but have little effect on the body's increased protein degradation. 4,5 Excessive caloric allotments may increase CO 2 production rates and thereby exacerbate the ventilatory burden of the child. 6 One study of ECMO neonates has shown a possible paradoxical increase in protein breakdown with the administration of increased carbohydrate regimens.…”
Section: Discussionmentioning
confidence: 99%
“…The increased allotment of protein in parenteral nutrition regimens serves to increase the synthesis of new protein but has little effect on elevated rates of protein breakdown. 4,5 Excessive carbohydrate provisions may worsen respiratory failure, 6 and a recent study of ECMO neonates has correlated increased carbohydrate intake with further increases in protein breakdown. 7 Therefore, investigation into an alternate means to alter protein metabolism in this cohort is clinically relevant.…”
mentioning
confidence: 99%
“…Neonates have high protein turnover rates of about 6 to 12 g/kg per day, in contrast to adults (3.5 g/kg per day). 25,26 Fortunately, amino acid supplementation is shown to improve protein balance in children and surgical patients by promoting protein synthesis. 21 In neonates with cardiopulmonary failure requiring ECMO, the protein turnover rate is doubled compared with stable patients.…”
Section: Protein Metabolism and Requirements During Stressmentioning
confidence: 99%
“…7,49 TrophAmine has also been associated with a decreased incidence and degree (level of serum direct bilirubin concentration) of PN-associated cholestasis. 50 The United States patent for TrophAmine expired in 2003, at which time Premasol (Baxter Healthcare Corp, Deerfield, IL) became available.…”
Section: April 2007mentioning
confidence: 99%